PERAN KERANGKA KONSEPTUAL AKUNTANSI DALAM PELAPORAN KEUANGAN PERUSAHAAN - Sembiring, Sabeth (UNIKA Santo Thomas, 2015)
Preparation of accounting theory is a sequential process that started from the determination reporting purposes and ends with preparation of accounting techniques. The conceptual framework is a coherent system-related purposes, the concept underlying the accounting, which is expected to lower the standards which are consistent in describing the nature, function, and limitations of accounting. This conceptual framework must be accepted by all parties concerned. Functions of this conceptual framework to enhance the comparability of financial statements and to evaluate the accounting practices. One benefit is the conceptual framework provides guidance that can provide guidance for standard setters. The contents of the general conceptual framework starts from the financial reporting purposes, the qualitative characteristics of accounting information, elements of financial statements, the measurement and recognition of financial reports, and presentation. Presentation of the conceptual framework includes reporting financial position, cash flow and liquidity reporting, and reporting earnings.